Assessing the Readiness of High School Geography Teachers for the Implementation of the 2018 General Education Curriculum - Minh, Le Anh Khanh; Dung, Mai Thi Thuy; Tuan, Nguyen Chi; Thanh, Ta Chi (VNU Journal of Science: Education Research; Vol 41 No 3, 2025)
The 2018 General Education Curriculum in Vietnam marks a significant shift towards competency-based education which requires teachers to adapt to new pedagogical approaches, curricula, and assessment methods. This research investigates the readiness of high school Geography teachers to implement the new curriculum, focusing on three key factors: knowledge, skills, and support. Using a mixed-methods approach, the study surveyed 205 teachers across 36 provinces. Findings reveal that while teachers acknowledge the importance of the reform, their readiness levels vary. Specifically, 59.5% believe that professional training enhances their knowledge, 63.9% consider pedagogical skills crucial, and 62% highlight the importance of support from educational authorities. Nonetheless, teachers still face challenges and require further support to effectively implement the new curriculum.